Room temperature ferromagnetism and ferroelectricity in strained multiferroic BiFeO3 thin films on La0.7Sr0.3MnO3/SiO2/Si substrates. (15th April 2017) - Ramírez-Camacho, M.C.; Sánchez-Valdés, C.F.; Gervacio-Arciniega, J.J.; Font, R.; Ostos, C.; Bueno-Baques, D.; Curiel, M.; Sánchez-Llamazares, J.L.; Siqueiros, J.M.; Raymond-Herrera, O.
Abstract: A novel ferromagnetic state coexisting with ferroelectric ordering at room temperature in strained BiFeO3 (BFO) thin films grown using a sputtering technique on La0.7 Sr0.3 MnO3 /SiO2 /Si(100) (LSMO/SOS) substrates is reported. The properties of BFO films with different thicknesses ( t BFO = 15, 50, 70, 120, and 140 nm) on 40 nm LSMO layers are explored. [012] out-of-plane highly textured BFO/LSMO stacks grew with rhombohedral structures. LSMO layers are nanostructured in nature, constituted by ferromagnetic single-domain nanoregions induced by the constrain of the SiO2 surface, with T C ∼200 K and high coercive field ( H C ) of ∼1100 Oe at 2.5 K. BFO films grew epitaxially nanostructured on LSMO, exhibiting ∼4 nm spherical nanoregions. The BFO layers show typical antiferromagnetic behavior (in a greater volume fraction) when made thicker ( t BFO > 70 nm). The thinner films ( t BFO < 50 nm) display ferromagnetic behavior with T C > 400 K, H C ∼ 1600 Oe for 15 nm and ∼1830 Oe for 50 nm. We propose that such ferromagnetic behavior is originated by the establishment of a new magnetic configuration in the Fe 3+ OFe 3+ sublattice of the BFO structure, induced by strong hybridization at the interface as consequence of superexchange coupling interactions with the ferromagnetic Mn 3+ OMn 3+ /Mn 4+ sublattice of LSMO. All BFO layers show excellent ferroelectric and piezoelectric properties (coercive field ∼ 740 kV/cm, and d 33 = 23 p.m./V for 50 nm; ∼200 kV/cm and 55 p.m./V for 140 nm), exhibiting 180° and 109° DWs structures depending on the thickness. Such multiferroic properties predict the potential realization of new magneto-electronic devices integrated with Si technology.